Kendala Anggota Legislatif Perempuan di DPRD Kota Medan Menghasilkan Kebijakan Berbasis Kesetaraan Gender - SYAFRUDDIN RITONGA; BEBY MASITHO BATUBARA; REHIA K ISABELLA BARUS (Politeia: Jurnal Ilmu Politik, 2015)
This research was conducted on the basis of gender inequalities are still many who manifests in various forms. It is necessary to process gender-based regulation in any policy formulation by the government. Strengthening the role of women legislators is an important step to accommo-date the various demands, rights, and aspirations of women so as to produce public policies based on gender equality. This research uses descriptive qualitative method to describe the ac-tivities of a female legislative involvement Medan in quantity and quality in the use of his posi-tion to generate gender-based public policy. The results of this study indicate that: 1.Lack of po-litical education of women-owned legislature; 2.Patriarchal culture that remains deeply em-bedded in the public field; 3.Less time to focus on politics; 4.Female legislative indifference to the condition of women in the city of Medan; 5.The notion that women rely more on emotional creatures. Its base on gender and political approach.Keywords: Legislature, public policy, gender inequalities.